Gender Differences in School Stress and Academic Satisfaction in Pre-Adolescents: The Role of Physical Activity - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Gender differences in school stress and academic satisfaction among pre-adolescents remain underexplored, particularly in relation to physical activity as a potential protective factor. This study aimed to examine these differences and investigate the role of sports/exercise frequency in mitigating boredom and stress, controlling for school safety, using a large multinational dataset. Methods: Data from the International Survey of Children s Well-Being (ISCWeB, third wave; N = 128,184 pre-adolescents aged 6-14 from 35 countries) were analyzed. Key variables included boredom and stress (0-10 scales), sports/exercise frequency (categorized as low: 0-2 days/week, medium: 3-4, high: 5-6), and school safety (0-4 scale). Descriptive statistics were stratified by gender and sports level. Multivariate analysis of variance (MANOVA) tested combined effects of sports level, gender, and their interaction, followed by univariate ANOVAs (Type II). Results: Modest gender differences were found in stress (boys: mean = 4.05; girls: mean = 4.16) and academic satisfaction (boys: 8.50; girls: 8.66), with similar distributions in physical activity variables. Higher sports frequency was associated with lower boredom (high: 4.00 vs. low: 4.46) and stress (high: 4.03 vs. low: 4.05). MANOVA confirmed a significant multivariate effect of sports level (Wilks lambda = 0.9984, F = 49.74, p < 0.0001), with marginal gender effect (p = 0.0525) and significant interaction (Wilks lambda = 0.9998, F = 6.59, p < 0.0001); effect sizes were small (partial eta(2) <= 0.014). School safety was a significant covariate (Wilks lambda = 0.9807, F = 1262.84, p < 0.0001, partial eta(2) approximate to 0.013). Conclusions: Physical activity modestly protects against school-related boredom and stress in pre-adolescents, with modest gender moderation. Findings support universal school programs promoting daily exercise, with gender-sensitive adaptations, to enhance emotional well-being and academic satisfaction.